Eichmann in Jerusalem. A Critical Dialogue - Kunath, Robert; Parvikko, Tuija (HannahArendt.net, 2024)
The editors of HannahArendt.net decided to facilitate this exchange and invited Tuija Parvikko to respond to some challenging remarks in Robert Kunath’s review. We hope that this dialogue was fruitful for both engaged scholars and will shed more light on the reviewed book and its topic, still raising controversies today.